Small petrosal approach to the middle portion of the mediobasal temporal region: Technical case report - (:unkn) unknown (ELSEVIER SCIENCE INC, 2004)
BACKGROUND The mediobasal temporal region has been divided into three portions: anterior, middle, and posterior. Surgical access, especially to the middle portion, presents a formidable challenge to neurosurgeons, and much controversy still exists regarding the selection of the surgical approach to this region. CASE REPORT We used the small petrosal approach to the middle portion of the mediobasal temporal region in a patient with intractable seizures caused by a cavernous angioma in this region. Using this approach, we selectively removed the lesion without postoperative deficits. CONCLUSION The small petrosal approach was found to be useful and safe as an alternative technique for selective removal of the lesion in the middle portion of the mediobasal temporal region. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: hippocampus; mediobasal temporal region; microsurgical anatomy; parahippocampal gyms; petrosal approach; VISUAL FIELD CHANGES; LOBE EPILEPSY; ARTERIOVENOUS-MALFORMATIONS; SUBTEMPORAL AMYGDALOHIPPOCAMPECTOMY; TRANSTENTORIAL APPROACH; MICROVASCULAR ANATOMY; PARAHIPPOCAMPAL GYRUS; MICROSURGICAL ANATOMY; SURGICAL-MANAGEMENT; OPTIC RADIATION